Performance, corpo e ação na composição musical - Mauro Rodrigues (2012)
This paper studies the relationship between performance and composition, as well as the musical performance as a process of transformation in which the body has a central place. This will be from a transdisciplinary approach, drawing on theory and reflection in the field of performing arts, especially in ethnoscenology and performancestudies, not stealing dialogue with related areas such as cognitive science, neuroscience, musicology, philosophy and anthropology, as sources of advice, confrontation and inspiration. The music plays a central role in the thesis and its appearance will be through the example of composition and performance of Suite para os Orixás, musicalpiece originally conceived in collaboration with musician Esdra Expedito Ferreira, Neném, for group and string orchestra that will be studied in terms of their composition and performance, emphasizing the processes of transformation as a result.